The abnormal flow behavior of Mg-9Gd-4Y-2Zn-0.5Zr alloy during hot tensile deformation at high temperature and low strain rate - Mu Meng; Xiaoying Wang; Jinbiao Zhang; Xingxing Chen; Genxing Lei; Zhaoming Yan; Zhimin Zhang (Journal of Materials Research and Technology)
Through hot tensile testing, the flow stress-strain curves of Mg-9Gd-4Y–2Zn-0.5Zr alloy after repetitive upsetting-extrusion (RUE) have been obtained. Under high-temperature and low-strain-rate conditions (450°C-0.0001s⁻1, 500°C-0.001s⁻1, and 500°C-0.0001s⁻1), the alloy exhibits excellent plasticity with elongation exceeding 300%, and stress progressively increases with strain in later deformation stages. The above phenomenon differs from the conventional flow behavior of magnesium alloys. The excellent plasticity is attributed to the coexistence of grain boundary sliding (GBS) and dislocation slip. Dislocation slip modes include basal slip, prismatic slip, and pyramidal <c+a> slip, with basal and pyramidal <c+a> slips alternating continuously to ensure the continual presence of multiple slips during deformation. GBS induced by dynamic recrystallization (DRX) is considered to belong to the core-mantle mechanism. Additionally, microcracks near large block-shaped long-period stacking ordered (LPSO) phases have been observed. As strain increases, these LPSO phases dissolve gradually, reducing their size and fraction, further enhancing plasticity. The increased flow stress in later stages is determined by deformed grains that undergo dislocation slip. The resistance to dislocation movement in deformed grains is increased by dislocation strengthening and solid solution strengthening. Simultaneously, the fraction of these deformed grains continuously increases due to grain growth during hot deformation.